Implementing the stability and growth pact: enforcement and procedural flexibility - Roel Beetsma; Xavier Debrun (European Central Bank (ECB), 2005)
The paper proposes a theoretical analysis illustrating some key policy trade-offs involved in the implementation of a rules-based fiscal framework reminiscent of the Stability and Growth Pact (SGP). The analysis offers some insights on the current debate about the SGP. Specifically, greater "procedural" flexibility in the implementation of existing rules may improve welfare, thus increasing the Pact's political acceptability. Here, procedural flexibility designates the enforcer's room to apply well-informed judgment on the basis of underlying policies and to set a consolidation path that does not discourage high-quality policy measures. Yet budgetary opaqueness may hinder the qualitative assessment of fiscal policy, possibly destroying the case for flexibility. Also, improved budget monitoring and greater transparency increase the benefits from greater procedural flexibility. Overall, we establish that a fiscal pact based on a simple deficit rule with conditional procedural flexibility can simultaneously contain excessive deficits, lower unproductive spending and increase high-quality outlays.
Keywords: E62; H6; 330; deficits; fiscal rules; procedural flexibility; Stability and Growth Pact; structural reforms; Theorie; EU-Staaten; Europäischer Stabilitätsmechanismus